ANALISIS METODE TOPSIS DALAM MENENTUKAN SMARTPHONE TERBAIK - Eka Hayana Hasibuan (LPPM Politeknik LP3I Medan, 2020)
Smartphones are mobile phones that are equipped with a variety of features and specifications that are beyond qualified normal function. Nowadays cell phones are not rare items because almost everyone in the world have cell phones especially people in Indonesia. Most of them already use smartphones and even making smartphones a primary need. In addition, software improvement and hardware for cellphones and smartphones is growing rapidly in order to meet market needs. Para vendors are aggressively releasing the latest products almost every day so that the number and types of smartphones increasingly diverse. Prices, features and specifications for each type of smartphone also vary. This is what causing potential consumers to be confused about what kind of smartphone is suitable for them because there are so many once an option is available. Based on this, it is necessary to build a support system decision to help determine the smartphone that fits the criteria and needs The method used in making the decision to choose the best smartphone is Topsis. The Topsis method is a multiple criteria decision making (MCDM) method TOPSIS is able to provide more consistent results compared to other methods and systems applying the TOPSIS method is easier to understand and use.